Sg- Continuity in Topological Spaces. - Darwesh, Halgwrd M.; O.Hassan, Nawroz (Sulaimani Journal for Pure and Applied Sciences, 2015)
The aim of the present paper, is to introduce and study a new class of functions which is strictly placed between the class of -continuous functions and the class of semi-continuous function, we call it the class of -continuous functions. The basic properties, characterizations and relationships with some other classes of continuity are also obtained.
Keywords: Sgopen set; Semiopen set; gclosed set; Sgcontinuous Function